Active right atrial emptying fraction predicts reduced survival and increased adverse events in childhood pulmonary arterial hypertension. (15th November 2018) - Kumar, Shine; Vadlamudi, Karunakar; Kaddoura, Tarek; Bobhate, Prashant; Goot, Benjamin H.; Elgendi, Mohamed; Jain, Shreepal; Colen, Timothy; Khoo, Nee Scze; Adatia, Ian
Abstract: Background: Right atrial (RA) function has been studied rarely in childhood pulmonary arterial hypertension (PAH). We sought to determine if RA and right ventricular (RV) area changes measured by echocardiography predicted outcomes. Methods: We reviewed data from children with PAH undergoing cardiac catheterization and echocardiography. RA and RV areas were obtained from the apical 4-chamber view. Clinical worsening indicated initiation of parenteral prostanoid therapy, heart and/or lung transplantation, Potts shunt surgery or death. Results: We studied 57 children (27 females), median age 3 years (range 0.30–17 years), body surface area 0.56 m2 (0.2–1.8), follow up 3 years (0.21–8.35), time to clinical worsening was 1.14 years (0.03–6.14) and mortality was 1.55 years (range 0.88–4.95). We determined from receiver operator curves that RA active emptying fraction (RA EaF) ≥60% predicted clinical worsening (sensitivity 78%, specificity 69%, AUC 0.7) and mortality (sensitivity 100%, specificity 65%, AUC 0.82). RV fractional area change (RVFAC) <25% predicted clinical worsening (sensitivity 72%, specificity 79%, AUC 0.85) and death (sensitivity 67%, specificity 69%, AUC 0.77). The combination of RA EaF ≥60% and RVFAC <33% were best predictors of clinical worsening (sensitivity 72%, specificity 82%, partial AUC 0.65) and mortality (sensitivity 100%, specificity 77%, partial AUC 0.75). Conclusion: In childhood PAH, RA EaF ≥ 60% and RVFAC <25% were associated with poor outcomes. RA EaF ≥60% and RVFAC <33% were best predictors of clinical worsening and may be useful markers in children with PAH who require closer observation and more intensive therapy. Highlights: In children with pulmonary hypertension predictors of clinical worsening and death were: Right atrial active emptying fraction ≥60% Right ventricular fractional area change < 33%